ATHE BRITISH FORWARD POLICY AND A CASE OF THE POLITICAL SYSTEM AND THE ADMINISTRATION OF DERA GHAZI KHAN DISTRICT 1849-1947 - Abdul Sattar Adnan; Dr. Nida Fatima; Naila Naz Lalwani; Nasiba Bibi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2023)
Dera Ghazi Khan was the part of Derajat before the annexation of Punjab in 1849 during Sikh rule. British forces crossed the Indus during the great game after 1840 and entered in North West Frontier Province. British forces also defeated Sikhs during the 2nd Sikh War in 1849 and occupied Punjab. Now they reached across the Indus and faced the different Baloch warrior tribes. When they reached here, these tribes continuously created troubles for the British Government and it was the need of time to bring peace in the area and maintain law and order in the region. Keeping in mind, the seriousness of the situation British Government made to use different policies to achieve their aims and objectives[i]. After the downfall of the Mughal Empire, British occupied the whole Indian Sub-Continent. Indian Sub-Continent ranges to the river Indus to the foot of the mountain ranges which separates the plains of the Indus valley from the plateaus of Afghanistan and Kalaat. These mountain ranges shaped a huge irregular of belt extending from the Khagan glen , west of Kashmir , round district of Peshawar, Kohat and Bannu and in a long stretched southward down the Indus valley to the Sindh seaboard near Karachi, measuring about 1200 miles[ii].